Payment transactions in international trade - Budak, Uygar (My University, 2007)
ULUSLARARASI TİCARETTE ÖDEME YÖNTEMLERİ Artan ihtiyaçlara, gelişen teknolojiye ve özellikle taşımacılık ve iletişim teknolojilerindeki gelişmeye bağlı olarak özellikle yirminci yüzyılın ikinci yarısında uluslararası ticaret büyük bir artış göstermiştir. Yapısı gereği önemli riskleri bünyesinde barındıran uluslararası ticaret farklı ülkelerde bulunan ve çok defa birbiri hakkında yeterli bilgiye sahip olmayan taraflar arasındaki satım sözleşmelerini konu edinmektedir. Yerel satım sözleşmelerinden farklı olarak uluslararası nitelikteki satım sözleşmelerinin yerine getirilmesinde tarafların edimlerini oluşturan malın teslimi ve bedelin ödenmesi aynı anda gerçekleştirilememektedir. Her iki tarafın karşı tarafın edimini öncelikli olarak beklemekteki çıkarı uluslararası ticarette güven problemini ortaya çıkarmıştır. Taraflar arasındaki güvensizlik ve uluslararası ticaretin bünyesindeki riskler uygulamada akreditifin doğumuna yol açmıştır. Bir ödeme yöntemi olan akreditif taraflar arasındaki güven problemini önemli ölçüde ortadan kaldırmıştır. Uygulamanın ortaya çıkardığı bir müessese olan akreditif, milli kanunlarca ayrıntılı olarak düzenlenmemiştir. Bu konuda birörnek yazılı kurallara duyulan ihtiyaç Milletlerarası Ticaret Odası’nın yayınladığı Akreditiflere İlişkin Birörnek Teamül ve Uygulamalar ile giderilmiştir. Bugün tüm dünyada bankalarca açılan akreditifler bu kurallara göre yürütülmektedir. Uluslararası Ticaretin ülkeler açısından önemi aşikardır. Uluslararası Ticarette en güvenilir ve en çok kullanılan ödeme yöntemi olan akreditif müessesesinin ve akreditiflere ilişkin birörnek kuralların bilinmesi gereğinin önemi açıktır. Bu çalışmada akreditifin önemi, yapısı, işleyişi, türleri ve hukuki niteliği ayrıntılı olarak incelenmiş, Milletlerarası Ticaret Odasının bu konudaki en son yayını olan 600 sayılı birörnek kuralların getirdiği yeniliklere dikkat çekilmiştir.

PAYMENT TRANSACTIONS IN INTERNATIONAL TRADE International trade has increased considerably during the second half of the twentieth century due to the increasing needs, developing technology and particularly due to the developments in transportation and communication. The subject matter of the international trade, which, by its nature involves considerable risks, is sale contracts where the parties are in different countries and do not have sufficient knowledge about each other. Unlike domestic sale contracts, in international sale contracts the debts of the parties –delivery of the goods and payment of the price- can not be effected at the same time. The interests of both of the parties in expecting the other side’s debt initially created the security problem in international trade. The lack of confidence between the parties and the risks inherent in international trade has led to the birth of documentary credit. The documentary credit, which is a payment method, has removed the security problem on a large scale. The documentary credit, which is an institution created by practice, has not been arranged in detail by national laws. In this respect, the need to written rules was met by Uniform Customs and Practice(UCP) promulgated by International Chamber of Commerce(ICC). Today, documentary credits issued by banks run according to those rules all over the world. The importance of international trade for the countries is evident. The importance of the requirement to understand documentary credits as the most secured and most widely used way of payment in international trade, and uniform customs and practices for documentary credits is obvious. In this study, both the importance of documentary credits, their structure, process, types and legal character have been examined in detail, and innovations made by the last revision of UCP600 published by ICC have been pointed out.
Keywords: Akreditif; Ödeme Yöntemleri; Uluslararası Ticaret